THE USE OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS IN THE PRACTICE OF THE DENTIST DEPENDING ON THE FEATURES OF THE PAIN SYNDROME - Shundryk, M.A.; Marchenko, I.Y.; Tkachenko, I.M.; Marchenko, V.Y. (World of Medicine and Biology, 2025)
A literature review was conducted on the results of clinical studies examining the characteristics of pain syndrome in dental practice for the selection of adequate pharmacotherapy using non-steroidal anti-inflammatory drugs. Retrospective review and analysis of domestic and foreign publications on the characteristics of pain syndrome, and determination of pain relief tactics with the use of nonsteroidal anti-inflammatory drugs were selected as research methods. The research results indicate that pain is the most prevalent symptom in dental practice. During the diagnostic process, it is essential to rule out non-dental causes of pain in the orofacial region. The results of the study show that pain is the most prevalent symptom in dental practice. During the diagnostic process, it is essential to exclude non-dental causes of pain in the orofacial area, while also considering the localization, duration, and nature of the pain, the stimuli that provoke it, and the results of auxiliary examinations. Acute pain requires adequate treatment to eliminate the risk of developing chronic pain syndrome. Nonspecific anti-inflammatory drugs are pathogenetically justified for the treatment of such patients, but it is necessary to individually select the dosage and duration of use, taking into account not only their effectiveness but also their safety.
Keywords: pain; nonsteroidal anti-inflammatory drugs; dentistry